2010
DOI: 10.1021/jm9017465
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Bupropion Analogues as Potential Pharmacotherapies for Smoking Cessation

Abstract: Bupropion (2a) analogues were synthesized and tested for their ability to inhibit monoamine uptake and to antagonize the effects of human α3β4*, α4β2, α4β4, and α1* nAChRs. The analogues were evaluated for their ability to block nicotine-induced effects in four tests in mice. Nine analogues showed increased monoamine uptake inhibition. Similar to 2a all but one analogue show inhibition of nAChR function selective for human α3β4*-nAChR. Nine analogues have higher affinity at α3β4*-nAChRs than 2a. Four analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 23 publications
(72 reference statements)
1
67
0
Order By: Relevance
“…Although four stereoisomers are expected, only two trans-diastereomers, SS-and RR-OHBUP, were detected in plasma and when synthesized de novo (Suckow et al, 1997;Carroll et al, 2010Carroll et al, , 2014. These data are consistent with the suggestion that steric hindrance reduces cyclization to the cis-diastereomers, (2R,3S)-and (2S,3R)-OHBUP, and favors the thermodynamically more stable trans-isomers .…”
Section: Chiral Pharmacokinetics Of Bupropion and Metabolitessupporting
confidence: 84%
“…Although four stereoisomers are expected, only two trans-diastereomers, SS-and RR-OHBUP, were detected in plasma and when synthesized de novo (Suckow et al, 1997;Carroll et al, 2010Carroll et al, , 2014. These data are consistent with the suggestion that steric hindrance reduces cyclization to the cis-diastereomers, (2R,3S)-and (2S,3R)-OHBUP, and favors the thermodynamically more stable trans-isomers .…”
Section: Chiral Pharmacokinetics Of Bupropion and Metabolitessupporting
confidence: 84%
“…The pharmacological activities [i.e., inhibitory potency (Table 1) and binding affinities (Table 2)] of BP, its natural metabolites, as well as (±)-SADU-3-72, a photoreactive BP derivative (Figure 1) for different AChR subtypes have been studied by in vitro approaches. In addition, functional studies have shown that BP and its analogs inhibit both muscle-and neuronal-type AChRs in the low to intermediate micromolar range [2,20] . The BP selectivity for different AChRs follows the sequence: 3-> 4-~ 1-> 7-containing AChRs (Table 1).…”
Section: Pharmacological Activity Of Bp and Its Metabolites And Derivmentioning
confidence: 99%
“…Moreover, BP induces locomotor stimulation, although this activity is mild [16][17][18] . BP has also been found to decrease not only nicotine but also the addictive and craving effects elicited by methamphetamine in humans [19] , and by cocaine in rodents [20] , as well as morphine-induced tolerance and dependence in rodents [21] .…”
Section: Introductionmentioning
confidence: 99%
“…In the benzoin-type condensation reaction, after the nucleophilic attack of the cyanide catalyst on the acylsilane, the mechanism involves a [1,2] shift of the migrating SiR3 group (Brook rearrangement), generating the key stabilized acyl anion equivalent, in analogy with the Breslow catalytic cycle.…”
Section: Methodsmentioning
confidence: 99%
“…α-Amino ketones are widespread structural moieties, common to both natural and synthetic significant compounds in medicinal chemistry ( Figure 1) [1][2][3][4]. They are largely employed as building blocks in the preparation of a large number of molecules, in particular, 1,2-aminoalcohols, and vicinal diamines (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%